Β-Endorphin Mediates the Development and Instability of Atherosclerotic Plaques. (28th March 2020) - Okano, Taisuke; Sato, Kengo; Shirai, Remina; Seki, Tomomi; Shibata, Koichiro; Yamashita, Tomoyuki; Koide, Ayaka; Tezuka, Hitomi; Mori, Yusaku; Hirano, Tsutomu; Watanabe, Takuya
Abstract : β -Endorphin, an endogenous opioid peptide, and its μ -opioid receptor are expressed in brain, liver, and peripheral tissues. β -Endorphin induces endothelial dysfunction and is related to insulin resistance. We clarified the effects of β -endorphin on atherosclerosis. We assessed the effects of β -endorphin on the inflammatory response and monocyte adhesion in human umbilical vein endothelial cells (HUVECs), foam cell formation, and the inflammatory phenotype in THP-1 monocyte-derived macrophages, and migration and proliferation of human aortic smooth muscle cells (HASMCs) in vitro. We also assessed the effects of β -endorphin on aortic lesions in Apoe −/− mice in vivo. The μ -opioid receptor (OPRM1) was expressed in THP-1 monocytes, macrophages, HASMCs, HUVECs, and human aortic endothelial cells. β -Endorphin significantly increased THP-1 monocyte adhesion to HUVECs and induced upregulation of intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and E-selectin via nuclear factor- κ B (NF- κ B) and p38 phosphorylation in HUVECs. β -Endorphin significantly increased HUVEC proliferation and enhanced oxidized low-density lipoprotein-induced foam cell formation in macrophages. β -Endorphin also significantly shifted the macrophage phenotype to proinflammatory M1 rather than anti-inflammatory M2 via NF- κ B phosphorylation during monocyte-macrophage differentiation and increased migration and apoptosis in association with c-jun-N-terminal kinase, p38, and NF- κ B phosphorylation in HASMCs. Chronic β -endorphin infusion into Apoe −/− mice significantly aggravated the development of aortic atherosclerotic lesions, with an increase in vascular inflammation and the intraplaque macrophage/smooth muscle cell ratio, an index of plaque instability. Our study provides the first evidence that β -endorphin contributes to the acceleration of the progression and instability of atheromatous plaques. Thus, μ -opioid receptor antagonists may be useful for the prevention and treatment of atherosclerosis.